(untitled) (Revista científica Olimpia, 2020)
Physical Education has as its main objective to contribute to the multilateral and harmonious development of the personality. In the achievement of this purpose, warming plays a determining role, considered by multiple researchers as a set of physical activities that are carried out before starting a physical education class and which aims to predispose the body for the most adequate performance in the face of a load. work, which for multiple reasons, is not always a moment of the teaching-learning process that is developed adequately by teachers. Based on this, the fundamental intention of this research is to design an exercise system to favor an adequate warm-up in correspondence with the current demands of the Physical Education class in the context of medical sciences, the psychological peculiarities of the students and the physical level reached. For this, methods of the theoretical, empirical and statistical level are used, which allow the diagnosis of the problem under investigation to be obtained and, based on these results, to design the system of exercises, which are subjected to the criteria of specialists to assess their feasibility of application.